Peran Orangtua Siswa Kelas VI Terhadap Pembelajaran Daring Penjasorkes di SD Negeri Kuripan Lor 02 Kota Pekalongan - Nizar Khoirul Umam (Journal of Physical Activity and Sports (JPAS), 2022)
In the role of parents who have grade VI children, because in the current circumstances parents must also take their role to explain the transition from elementary school to the next level, in addition, grade VI students are required to prepare for elementary school graduation tests, junior high school entrance tests and adjustment processes. The method used in this research is a qualitative research method. Informants in this study are parents / guardians of class VI students and teachers learning SD N Kuripan Lor 02. The purpose of this study is to see how the role of parents during learning / school at home through online in guiding and supervising their children. The role of parents is so much in guiding children. Based on the results of the interview explained, the author can conclude that the role of parents to learn / online school is about how as parents should be able to provide encouragement, support, and motivation to children so that they remain passionate in learning / school at home. Pay attention to each task, and provide facilities related to learning / school learning penjasorkes. Accompany their learning/school activities or give them opportunities to explore their potential related to sports. Communicate assignments and exams with the teacher learning at the school. Keywords: Role Parents, Online Learning, Physical Education Elementary School Abstrak Pada peran orangtua yang memiliki anak kelas VI, karena pada keadaan saat ini orangtua juga harus mengambil perannya untuk menjelaskan peralihan dari sekolah dasar menuju jenjang selanjutnya, selain itu siswa kelas VI diwajibkan untuk mempersiapkan diri untuk tes kelulusan sekolah dasar, tes masuk sekolah menengah pertama dan proses penyesuaian diri. Metode yang digunakan dalam penilitian ini yaitu metode penelitian kualitatif. Informan dalam penelitian ini yaitu orangtua/wali murid kelas VI dan guru pembelajaran penjasorkes SD N Kuripan Lor 02. Tujuan penelitian ini yaitu untuk melihat bagaimana peran orang tua selama belajar/sekolah di rumah melalui daring dalam membimbing dan melakukan pengawasan terhadap anaknya. peran orang tua begitu banyak dalam membimbing anak. Berdasarkan hasil wawancara yang dijelaskan maka penulis dapat meyimpulkan bahwa peran orangtua terhadap belajar/sekolah daring yaitu tentang bagaimana cara sebagai orang tua harus bisa memberikan semangat, dukungan, serta motivasi kepada anak agar mereka tetap semangat dalam belajar/sekolah di rumah. Memperhatikan setiap tugasnya, dan memberikan fasilitas yang berkaitan dengan belajar/sekolah pembelajaran penjasorkes. Menemani kegiatan belajar/sekolah mereka atau memberikan peluang kepada mereka menggali potensi mereka yang berhubungan dengan olahraga. Mengkomunikasikan tugas maupun ujian dengan guru pembelajaran penjasorkes di sekolah. Kata kunci: Peran Orangtua, Belajar Daring, Pendidikan Jasmani Sekolah Dasar